Diseño e implementación del sistema de control de temperatura de planta pasteurizadora de leche en la Universidad Antonio Nariño sede Cartagena (2023)
This document describes the process of designing and implementing an automatic temperature control system for a milk pasteurizing plant. Pasteurization is done under the HTST (High Temperature Short Time) technique, which contemplates processing raw milk at a temperature between 70º – 75ºC for a period of 15 – 30 seconds. Although the pasteurization standards established in Decree 616 of 2006 define heating points for each particle at 72°C - 76°C for 15 seconds, from 71.7°C to 76 for 15 seconds for this type of pasteurization, to achieve a reduction of pathogenic agents more efficiently and without losing the nutritional properties of the milk. The heating process is done through three (3) flat plate heat exchangers, where a liquid (water) is heated in the service boiler for heat transfer to the milk to be pasteurized. The first exchanger performs the function of preheating the milk, in the second the temperature is raised up to the pasteurization range (70º – 75ºC). The third exchanger serves as a temperature holder during the 15 seconds. The pasteurizing plant has temperature sensors at different points in the process that allow effective temperature control. In addition to electric pumps for the circulation of both liquids (water and milk). The control process was implemented by means of a Siemens S7 1200 PLC, which controls the temperature and the level of the boiler water, the on and off of pumps. The monitoring of the variables is carried out on a Siemens HMI screen.